Application of mesenchymal stem cells during machine perfusion: an emerging novel strategy for organ preservation - Li, Jiale; Peng, Qinbao; Yang, Ronghua; Li, Kunsheng; Zhu, Peng; Zhu, Yufeng; Zhou, Pengyu; Szabó, Gábor; Zheng, Shaoyi (Frontiers in immunology, 2021)
Although solid organ transplantation remains the definitive management for patients with end-stage organ failure, this ultimate treatment has been limited by the number of acceptable donor organs. Therefore, efforts have been made to expand the donor pool by utilizing marginal organs from donation after circulatory death or extended criteria donors. However, marginal organs are susceptible to ischemia-reperfusion injury (IRI) and entail higher requirements for organ preservation. Recently, machine perfusion has emerged as a novel preservation strategy for marginal grafts. This technique continually perfuses the organs to mimic the physiologic condition, allows the evaluation of pretransplant graft function, and more excitingly facilitates organ reconditioning during perfusion with pharmacological, gene, and stem cell therapy. As mesenchymal stem cells (MSCs) have anti-oxidative, immunomodulatory, and regenerative properties, mounting studies have demonstrated the therapeutic effects of MSCs on organ IRI and solid organ transplantation. Therefore, MSCs are promising candidates for organ reconditioning during machine perfusion. This review provides an overview of the application of MSCs combined with machine perfusion for lung, kidney, liver, and heart preservation and reconditioning. Promising preclinical results highlight the potential clinical translation of this innovative strategy to improve the quality of marginal grafts.
Gesehen am 30.09.2022